Interspecific differences in tree growth and mortality responses to environmental drivers determine potential species distributional limits in Iberian forests - Benito-Garzón, Marta; Ruíz-Benito, PALOMA; Zavala, Miguel A. (Global Ecology and Biogeography, 2013)
Aim Tree growth may be enhanced by carbon dioxide fertilization unless drought stress becomes too severe, yet the likely increase in tree growth under a warmer climate is still controversial. Tree mortality has increased in some regions, but its multifactorial nature makes the prediction of likely global trends difficult. The aims of this work are: (1) to assess which abiotic, structural and competition factors influence tree growth and tree mortality in mainland Spain, and (2) to evaluate whether these processes would drive species distributions and would improve current niche model predictions. Location Continental Spain. Methods We projected species distributional models by integrating nonparametric tree growth and tree mortality models based on repeated surveys of diameter at breast height and mortality for 40,721 trees distributed in 45,301 plots, which include the 11 most common canopy tree species in continental Spain, as measured in the second and third National Forest Inventories, with a mean lag time of 11 years. Results Tree growth and tree mortality were explained by an assemblage of many factors, among which climate and competition played a key role. The accuracy of models including tree growth and tree mortality in predicting tree habitat suitability was comparable to classical niche models based on species occurrence. Projections under climate change showed for 9 out of 11 species, a likely increase in tree growth that would be counteracted by an increase in tree mortality, suggesting that even if growth rates increase, mortality would limit the species ranges under global warming expectations. Main conclusions Growth and mortality are major determinants of species distributions. Under future climate change expectations, our model suggests that growth may increase for some Iberian species, but even in this case, species ranges at the rear edge would be limited by an increase in mortality rates.
Keywords: climate change; demographic rates; national forest inventory; phenotypic variability; Spain; species distributional models; tree growth; tree mortality

Patterns and drivers of regeneration of tree species in forests of peninsular Spain - Vayreda, Jordi; Gracia, Marc; Martínez-Vilalta, Jordi; Retana, Javier (Journal of Biogeography, 2013)
Aim Our study aimed to identify and explore the main factors that influence tree recruitment of multiple species at a regional scale across peninsular Spain, an understanding of which is essential for predicting future forest species composition in the face of ongoing environmental change. The study focused on the dynamics of the key transition phase from saplings to adult trees. Location The forests of peninsular Spain. Methods We used the extensive network of plots sampled in two consecutive Spanish national forest inventories (> 30,000 plots) to identify the factors that determine regeneration patterns of the 10 most abundant forest species of Spain at relatively large temporal (c. 10 years) and spatial scales (across Spain): five coniferous species of Pinus (pines) and five broadleaved species of the genera Fagus and Quercus. We fitted separate generalized linear models for the pine species and the broadleaved species to assess the response of sapling abundance and ingrowth rate to the spatial variability of climate (temperature, water availability and recent warming), forest structure (tree density, understorey and overstorey canopy cover, and basal area change) and disturbances (previous forest logging, wildfires and grazing). Results Mean sapling abundance was four times higher for broadleaved species than for pines, while mean annual ingrowth was twice as high. Sapling abundance and ingrowth rate were mainly determined by stand structure, both in pines and broadleaved trees. The direct effects of disturbances and climate were comparatively smaller, and there was no detectable effect of recent warming. Main conclusions The higher values of ingrowth rate of broadleaved species can be explained by their ability to maintain a higher sapling bank due to their greater shade tolerance. This differential response of pines and broadleaved species to canopy closure suggests a probable increase in broadleaved species at the expense of pines. This transition could occur earlier in stands with faster canopy closure dynamics. Spatially explicit, mixed-species demographic models incorporating both the ingrowth and the tree mortality components are needed for predicting the composition of future forests.
Keywords: Broadleaved trees; climate warming; conifers; disturbance; ingrowth rate; national forest inventory; sapling abundance; shade tolerance; Stand Structure; Water availability

Spatial Patterns and Predictors of Forest Carbon Stocks in Western Mediterranean - Vayreda, Jordi; Gracia, Marc; Canadell, Josep G; Retana, Javier (Ecosystems, 2012)
Mediterranean semi-arid forest ecosystems are especially sensitive to external forcing. An understanding of the relationship between forest carbon (C) stock, and environmental conditions and forest structure enable prediction of the impacts of climate change on C stocks and help to deﬁne management strategies that maximize the value of forests for C mitigation. Based on the national forest inventory of Spain (1997–2008 with 70,912 plots), we estimated the forest C stock and spatial variability in Peninsular Spain and, we determined the extent to which the observed patterns of stand C stock can be explained by structural and species richness, climate and disturbances. Spain has an average stand C stock of 45.1 Mg C/ha. Total C stock in living biomass is 621 Tg C (7.8% of the C stock of European forests). The statistical models show that structural richness, which is driven by past land use and life forest history including age, development stage, management activities, and disturbance regime, is the main predictor of stand tree C stock with larger C stocks in structurally richer stands. Richness of broadleaf species has a positive effect on both conifer and broadleaf forests, whereas richness of conifer species shows no signiﬁcant or even a negative effect on C stock. Climate variables have mainly an indirect effect through structural richness but a smaller direct predictive ability when all predictors are considered. To achieve a greater standing C stock, our results suggest promoting high structural richness by managing for uneven-aged stands and favoring broadleaf over conifer species.
Keywords: conifer and broadleaf forests; fire disturbance; Forest management; national forest inventory; Peninsular Spain; structural richness; tree carbon stock; Tree species richness; understory carbon stock; Water availability

Combination of structural and compositional factors for describing forest types using national forest inventory data - Rego, F; Godinho-Ferreira, P; Uva, J S; Cunha, J (Monitoring and Indicators of Forest Biodiversity in Europe - From Ideas to Operationality, 2005)
For the first time in Portugal, simple variables describing the vertical structure and the composition of forests on the Portuguese mainland were included in the 2258 sample plots of the National Forest Inventory (DGF 2001). The vertical forest structure was assessed by percentage cover of seven height. classes and the composition of the different layers was described using plant species, or groups of plant species, easily identifiable in the field. Cluster analysis, in particular K-means statistics, was performed using combinations of vertical structure and compositional data, resulting in ten main natural groups or forest types: 1) Quercus pyrenaica forests; 2) Other deciduous oak forests; 3) Arbutus unedo forests; 4) Cistus shrubs; 5) Cytisus shrubs; 6) Acacia forests; 7) Quercus suber forests; 8) Pinus pinaster forests; 9) Eucalyptus forests; and 10) Other forests. The last four groups were further subdivided according to the vertical structure resulting in twenty final forest types. The geographical distribution of these forests types and the implications for biodiversity and other forest issues are presented and discussed.
Keywords: Biodiversity; composition; forest types; national forest inventory; vertical structure

Combination of structural and compositional factors for describing forest types using national forest inventory data - Rego, F.; Godinho-Ferreira, P.; Uva, J. S.; Cunha, J. (Monitoring and Indicators of Forest Biodiversity in Europe - From Ideas to Operationality, 2005)
For the first time in Portugal, simple variables describing the vertical structure and the composition of forests on the Portuguese mainland were included in the 2258 sample plots of the National Forest Inventory (DGF 2001). The vertical forest structure was assessed by percentage cover of seven height. classes and the composition of the different layers was described using plant species, or groups of plant species, easily identifiable in the field. Cluster analysis, in particular K-means statistics, was performed using combinations of vertical structure and compositional data, resulting in ten main natural groups or forest types: 1) Quercus pyrenaica forests; 2) Other deciduous oak forests; 3) Arbutus unedo forests; 4) Cistus shrubs; 5) Cytisus shrubs; 6) Acacia forests; 7) Quercus suber forests; 8) Pinus pinaster forests; 9) Eucalyptus forests; and 10) Other forests. The last four groups were further subdivided according to the vertical structure resulting in twenty final forest types. The geographical distribution of these forests types and the implications for biodiversity and other forest issues are presented and discussed.
The following values have no corresponding Zotero field: periodical: Monitoring and Indicators of Forest Biodiversity in Europe - From Ideas to Operationality issue: 51 pub-location: TORIKATU 34, FIN-80100 JOENSUU, FINLAND
Keywords: Biodiversity; composition; forest types; national forest inventory; vertical structure